2014
DOI: 10.1002/ijc.29244
|View full text |Cite
|
Sign up to set email alerts
|

EPHB4 tyrosine‐kinase receptor expression and biological significance in soft tissue sarcoma

Abstract: Soft tissue sarcomas (STS) are heterogeneous malignant tumors of mesenchymal origin. Due to low incidence and high number of different histological subtypes, their pathogenesis and thus potential targets for their therapy remain barely investigated. Several studies revealed significant higher EPHB4 expression in malignancies such as prostate and colorectal cancer showing survival advantages for these tumor cells. Therefore we studied the expression of EPHB4 in a total of 46 clinical human specimens of differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…NVP is a small molecule that selectively inhibits tyrosine kinase activity of EphB4 (45). Becerikli et al (46) showed that NVP inhibited EphB4 autophosphorylation, reduced cell growth rate of synovial sarcoma, and fibrosarcoma cells in vitro and hampered sarcoma lung metastasis in vivo. Inhibition of EphB4 by NVP overcomes the acquired resistance to cisplatin in melanoma xenograft models (47).…”
Section: Discussionmentioning
confidence: 99%
“…NVP is a small molecule that selectively inhibits tyrosine kinase activity of EphB4 (45). Becerikli et al (46) showed that NVP inhibited EphB4 autophosphorylation, reduced cell growth rate of synovial sarcoma, and fibrosarcoma cells in vitro and hampered sarcoma lung metastasis in vivo. Inhibition of EphB4 by NVP overcomes the acquired resistance to cisplatin in melanoma xenograft models (47).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, knockdown of EphA2 expression has been observed to inhibit gastric cancer cell proliferation and invasion in vitro and in vivo (43). An additional study (44) demonstrated that EphB4-targeting siRNA decreases non-small cell lung cancer cell viability and the volume of established tumors in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Many sarcoma subtypes belonging to both these categories show aberration and/or mutation in signal transduction pathways, particularly defects in receptor tyrosine kinase (RTK) signaling [ 34 , 35 ]. Recent evidence suggests involvement of RTKs such as PDGFR [ 29 , 36 , 37 ], c-Met [ 38 ], Axl [ 39 ], IGF1-R [ 40 ], EphB4 [ 41 ] and ErbB4 [ 42 ] as driver kinases in different sarcoma subtypes including synovial sarcoma, Ewing sarcoma as well as malignant peripheral nerve sheath tumor (MPNST). Detailed phosphoproteomic analysis from cell lines and patient tumors also revealed involvement of RTKs such as PDGFR, Eph receptors, Axl, c-Met and IGF1-R [ 9 ] as potential driver kinases in sarcomas.…”
Section: Discussionmentioning
confidence: 99%